Policy recommendations for sustainable urban development of Khon Kaen Municipality, Thailand - Hngokchai , Phramahawasan; Chueasraku, Chinnawat (Journal of Politics and Governance, 2025)
The aim of this research is to provide policy recommendations for the sustainable urban development of Khon Kaen Municipality. The research methodology employs a qualitative approach utilizing a selective sampling method, which includes interviewees from four diverse sectors: government agencies, civil society, educational institutions, and the industry/ private sector. A total of eight informants participated in the study. The research focuses on three key components; smart city initiatives, network partnerships, and administration—as variables contributing to sustainable urbanization. The result from a study identified three key dimensions crucial for the sustainability of cities: firstly, building Sustainable Urbanization by Becoming a Smart City. Leveraging smart technologies is essential for improving residents' quality of life. This involves enhancing public services and urban infrastructure through digital solutions, such as optimizing transportation systems, energy consumption, and waste management. Secondly, building Sustainable Urbanization with Network Partnership. Fostering community engagement is vital for social cohesion and economic resilience. This includes supporting local businesses, creating innovation hubs, and organizing activities that bring residents together. Building strong community networks enhances social ties and economic opportunities. Lastly, Building a Sustainable City through Administration. Effective management of natural and economic resources is crucial for long—term sustainability. Administrative strategies should promote awareness about environmental conservation, optimize resource usage, and implement policies that ensure sustainable urban development. While, Administrations should focus on the optimal allocation and utilization of resources to create a harmonious and responsible urban society. Furthermore, organizing educational activities to raise awareness about natural resource management and promoting social and community events to strengthen relationships are key for preparing the urban population for future challenges. This structured approach aligns with existing research on sustainable urban development, emphasizing the integration of smart city technologies, community engagement through network partnerships, and efficient administration as pillars for building sustainable cities.